The Effects of Tax Avoidance, Audit Quality, Board Size, and Managerial Ownership on Investment Efficiency: Profitability as a Moderating Variable - Dini Destiara Ekaputri; Unggul Purwohedi; I Gusti Ketut Agung Ulupui (Pusat Publikasi Nusantara, 2026)
Investment efficiency is a critical determinant of corporate value creation, particularly in capital-intensive industries such as shipping, where strategic capital allocation directly affects long-term competitiveness. However, investment decisions are often influenced by corporate governance mechanisms and financial policies, including tax avoidance, audit quality, board size, managerial ownership, and profitability. This study aims to examine the effects of tax avoidance, audit quality, board size, and managerial ownership on investment efficiency, while investigating the moderating role of profitability. A quantitative research design was employed using secondary panel data collected from 25 shipping companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period, yielding 100 firm-year observations. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and Moderated Regression Analysis (MRA). The findings reveal that tax avoidance significantly enhances investment efficiency, whereas audit quality, board size, and managerial ownership do not exert significant direct effects. Profitability significantly strengthens the relationships between tax avoidance, managerial ownership, and board size with investment efficiency but does not moderate the relationship between audit quality and investment efficiency. The regression model is statistically significant and explains 30.2% of the variation in investment efficiency. These findings highlight the importance of strategic tax management and profitability in improving investment efficiency while emphasizing the need to strengthen governance effectiveness beyond structural corporate mechanisms.